PERBANDINGAN HASIL PELEDAKAN OVERBURDEN METODA KONVENSIONAL DENGAN METODA AIRDECK di PT BHUMI RANTAU ENERGI KABUPATEN TAPIN PROVINSI KALIMANTAN SELATAN - Aldi Suganda Putra; Tri Gamela Saldy (Departemen Teknik Pertambangan FT UNP, 2023)
Coal is one of the leading commodities in Indonesian mining, especially in the Sumatra and Kalimantan areas where coal reserves in these areas are very abundant. With the abundance of mining materials, especially coal, the mining industry is growing rapidly and making the mining industry a contributor to state income. In the mining industry, it is very common to find rocks that are quite hard or relatively hard which cannot be dug directly. To deal with this problem, dispersal of excavated materials is carried out using the blasting method. Scattering is not only for excavated materials but also for the covering layer of excavated materials. PT. Bhumi Rantau Energi itself uses conventional blasting and airdeck methods to dismantle the overburden. Many factors can influence blasting results, starting from geometric errors, not optimal powder factors, and so on. The less than optimal fragmentation results from the blasting carried out by PT. Bhumi Rantau Energi meant that the production target of 954,218 BCM was not achieved, but only around 674,121 BCM was achieved or only around 70%. The powder factor produced from conventional blasting is 0.14 kg/bcm while airdeck blasting produces a pf of 0.09 kg/bcm. Working time for conventional blasting is an average of 43 minutes and 71 minutes for airdeck blasting.